2013
DOI: 10.1016/j.vaccine.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

What college women know, think, and do about human papillomavirus (HPV) and HPV vaccine

Abstract: Participants were a convenience sample of college women (n=384) ages 18 to 26 attending a large, public university in Southern California. An electronic self-administered survey was utilized to collect data. The theory of planned behavior provided a framework for understanding the factors associated with vaccine uptake and with post-vaccine sexual behaviors. Results: College women had good HPV/HPV vaccine knowledge. Over 90% of vaccinees and non-vaccinees knew that Pap test is still needed after the vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 41 publications
(89 reference statements)
2
23
0
Order By: Relevance
“…However, the regression weight was negative (β = −0.73 to −0.71), contrary to TPB prevention studies, which found significant positive regression weights (β = 0.27 to 0.61; Askelson et al, 2010;Teitelman et al, 2011). One study observed that women might have entertained novel cognitions (i.e., thoughts of getting a vaccination) during questionnaire completion (Ratanasiripong et al, 2013), which may raise barrier perception, such as lack of time (Markovic et al, 2005) and affordability (Taylor et al, 2002), thus implying low control. From an empirical perspective, the negative regression weights for perceived behavioral control are likely due to the suppression phenomenon (Velicer, 1978).…”
Section: Discussionmentioning
confidence: 89%
“…However, the regression weight was negative (β = −0.73 to −0.71), contrary to TPB prevention studies, which found significant positive regression weights (β = 0.27 to 0.61; Askelson et al, 2010;Teitelman et al, 2011). One study observed that women might have entertained novel cognitions (i.e., thoughts of getting a vaccination) during questionnaire completion (Ratanasiripong et al, 2013), which may raise barrier perception, such as lack of time (Markovic et al, 2005) and affordability (Taylor et al, 2002), thus implying low control. From an empirical perspective, the negative regression weights for perceived behavioral control are likely due to the suppression phenomenon (Velicer, 1978).…”
Section: Discussionmentioning
confidence: 89%
“…However, few studies have explored the content of such conversations from the perspectives of adolescents, parents, and clinicians. Furthermore, although studies have examined perceptions of the HPV vaccine among youth[1518] and parents,[15, 19, 20], little is known about perceived informational needs of 11–12 year-old girls and how those compare to the needs of parents. Understanding what information about HPV vaccines girls and mothers believe to be important could enhance clinician delivery of developmentally appropriate vaccine-related messages, which may lead to improved vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with female undergraduates have examined demographic and psychosocial correlates of HPV vaccine receipt and intentions (Lindley et al, 2013; Ratanasiripong et al, 2013); however, an important gap in the literature is the examination of their relationship to a range of protective and risky health behaviors. Identifying relationships between health behaviors will inform the development of interventions targeting multiple health behaviors (e.g.…”
mentioning
confidence: 99%